2019
DOI: 10.1016/j.bbmt.2018.12.768
|View full text |Cite
|
Sign up to set email alerts
|

Recipients Receiving Better HLA-Matched Hematopoietic Cell Transplantation Grafts, Uncovered by a Novel HLA Typing Method, Have Superior Survival: A Retrospective Study

Abstract: HLA matching at an allelic-level resolution for volunteer unrelated donor (VUD) hematopoietic cell transplantation (HCT) results in improved survival and fewer post-transplant complications. Limitations in typing technologies used for the hyperpolymorphic HLA genes have meant that variations outside of the antigen recognition domain (ARD) have not been previously characterized in HCT. Our aim was to explore the extent of diversity outside of the ARD and determine the impact of this diversity on transplant outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 27 publications
0
80
2
6
Order By: Relevance
“…Determining the sequence of HLA proteins expressed by a recipient or donor by exon typing without ambiguity in the second field is considered sufficient for current clinical practice . However, our understanding of the impact of polymorphisms in coding positions out of the peptide‐binding groove, in non‐coding regions on HLA expression, disease susceptibility, and transplantation outcomes is continuing to evolve, and new perspectives in terms of NGS applications are emerging . Moreover, nucleotide substitutions, insertions, and deletions in the enhancer–promoter, intron, and 3′‐UTR regions can result in null alleles requiring identification in clinical settings …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the sequence of HLA proteins expressed by a recipient or donor by exon typing without ambiguity in the second field is considered sufficient for current clinical practice . However, our understanding of the impact of polymorphisms in coding positions out of the peptide‐binding groove, in non‐coding regions on HLA expression, disease susceptibility, and transplantation outcomes is continuing to evolve, and new perspectives in terms of NGS applications are emerging . Moreover, nucleotide substitutions, insertions, and deletions in the enhancer–promoter, intron, and 3′‐UTR regions can result in null alleles requiring identification in clinical settings …”
Section: Introductionmentioning
confidence: 99%
“…7 However, our understanding of the impact of polymorphisms in coding positions out of the peptide-binding groove, in non-coding regions on HLA expression, disease susceptibility, and transplantation outcomes is continuing to evolve, and new perspectives in terms of NGS applications are emerging. [9][10][11][12] Moreover, nucleotide substitutions, insertions, and deletions in the enhancer-promoter, intron, and 3 0 -UTR regions can result in null alleles requiring identification in clinical settings. 13 NGS methods are based principally on the following steps: immobilization of the DNA sample onto a solid support, cyclic sequencing reactions at the clonal level using automated fluidic devices, and detection of millions of simultaneous molecular events.…”
mentioning
confidence: 99%
“…Researchers have now demonstrated that typing HLA to the fourth field reveals previously “hidden” haplotypes, such as B*07:02:01~C*07:02:01:03, B*07:06:01~07:02:01:01 . With the ability to determine variation to this level of resolution, more distinct HLA associations and additional variation that is of clinical relevance, may become apparent . In addition, there is a lack of replication of results, in part due to the very large, genotyped, cohorts required to conduct accurate and robust GWAS studies.…”
Section: Discussionmentioning
confidence: 99%
“…116 With the ability to determine variation to this level of resolution, more distinct HLA associations and additional variation that is of clinical relevance, may become apparent. 116,117 In addition, there is a lack of replication of results, in part due to the very large, genotyped, cohorts required to conduct accurate and robust GWAS studies. Beyond this there have been concerns raised over the ability of GWAS studies to identify biologically important genes/genotypes due to complex genomic interactions, something highly relevant to the HLA region.…”
Section: Anti-tnf Monoclonal Antibodiesmentioning
confidence: 99%
“…The current state-of-the-art methods use next generation sequencing (NGS) to sequence a subset of exons in several HLA genes and result in a high-resolution "HLA type" that specifies the sequence in these exons. 1 Recently, a new method to characterize the HLA at even higher resolution was shown to have the potential to improve outcomes in transplantation in a retrospective study 2 . Other genes in the MHC are also important for transplantation 3 , HIV infection 4 , and many other diseases 5 .…”
Section: Introductionmentioning
confidence: 99%